Assessment of Light Fluctuations of LED Lamp at Different Pulse Mode Regulation Methods - Tetervenoks, O.; Galkin, I. (Elektronika ir Elektrotechnika, 2014)
Solid state lighting at this moment looks the most promising among other lighting technologies. One of the advantages of LEDs is the ability to change light output of LED in wide range. Different light regulation techniques have been discussed previously in the literature: fluent (amplitude mode), step and pulse mode regulation techniques. Pulse mode regulation method is one of the simplest, however, the significant drawback such as stroboscopic effect, has been mentioned previously in the literature. The aim of this paper is to evaluate light fluctuations (and undesired stroboscopic effects) of LED lamps operating under different pulse mode light regulation approaches as well as to found the conditions to accomplish acceptable level of this effect. The evaluation criteria of light fluctuations are discussed at the beginning of this article. Then the different pulse mode regulation approaches are described. The results of experiments and the conclusions are discussed at the end of the paper. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7265